2016
DOI: 10.1002/pip.2734
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of spatially resolved photoluminescence and viscoelastic mechanical properties of encapsulating EVA in differently aged PV modules

Abstract: The photoluminescence of ethylene vinyl acetate (EVA) in aged photovoltaic modules shows specific spatial patterns on the scale of the cells in the module that depend on the aging conditions. It is the aim of this work to investigate the correlation of these photoluminescence patterns to the viscoelastic mechanical properties of the encapsulating EVA.For this, the degradation under various conditions of two specimen sets of polycrystalline silicon photovoltaic minimodules, comprising EVA as encapsulating polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 82 publications
(118 reference statements)
2
25
0
Order By: Relevance
“…Our own results as well as detailed studies by Schlothauer et al [47,49] confirm that in the photobleached areas, the polymeric encapsulant is chemically changed due to the oxidative reaction of the polymer, leading to chain scission and consequently, to changes in the viscoelastic mechanical properties and thermomechanical properties of the polymer.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our own results as well as detailed studies by Schlothauer et al [47,49] confirm that in the photobleached areas, the polymeric encapsulant is chemically changed due to the oxidative reaction of the polymer, leading to chain scission and consequently, to changes in the viscoelastic mechanical properties and thermomechanical properties of the polymer.…”
Section: Discussionsupporting
confidence: 79%
“…The fluorescence effects observed upon DH storage (high temperature, high humidity, no irradiation) above permeable backsheets were correlated with the ingress of water vapour [34][35][36]51,52] and its interaction with the polymeric encapsulant and had a different origin from the irradiation-induced fluorescence effects [22,[49][50][51]. The intensity of this type of fluorescence is lower, and fluorescence spectroscopic measurements have shown that the absorption maximum of elevated temperature and water induced fluorescence lies at a lower wavelength than for irradiation induced fluorescence, as described in detail by Röder and Schlothauer in several scientific presentations [33,36,45,50,53].…”
Section: Discussionmentioning
confidence: 99%
“…That means that the elasticity in the EVA changes more with temperature compared with the BS. Similar elasticity values for unexposed and aged EVA encapsulant foils have been reported in the literature, where it is shown that the modulus drops considerably after 40 • C and tends to reach values below 1 MPa at temperatures higher than T m. 2,7 Overall, the results show that the changes in the elastic modulus of the foils are much higher than the changes in density and thickness measured within the temperature range studied.…”
Section: 2supporting
confidence: 87%
“…[2][3][4][5] While nondestructive quality testing of PV modules is necessary to qualify individual components embedded, for example, after manufacturing or upon problems in field performance, the characterization of the properties of BS and encapsulation foils inside a PV module is challenging. 6 On the one hand, the mechanical characterization of these foils commonly rely on destructive techniques, such as tensile tests 3 and dynamic mechanical analysis, 7 which potentially restrict further tests in case intact modules are required. Moreover, attempting to extract and separate the laminated module components before their individual characterization is difficult 2 and would incur severe material damage, which inevitably affects the results.…”
mentioning
confidence: 99%
See 1 more Smart Citation